Piers-Rubinsztajn Reaction and the Application in Siloxane/Polysiloxane Chemistry - Peng, Jiajian; Bai, Ying; Li, Jiayun (Letters in Organic Chemistry, 2019)
By using the Piers-Rubinsztajn processes, elastomers, foams, silicone surfactants and copolymers with alkoxy-functional arylamines and ethers can be prepared. The preparation and applications of siloxane-based materials through Piers-Rubinsztajn reaction synthesis pathway have been reviewed.
Keywords: Piers-Rubinsztajn reaction